No Effect of Adjunctive Minocycline Treatment on Body Metabolism in Patients With Schizophrenia. Issue 2 (April 2018) - Liu, Fang; Xie, Liqin; Zhang, Bingkui; Ruan, Ye; Zeng, Yong; Xu, XiuFeng; Zhao, Jingping; Fan, Xiaoduo
Abstract: Purpose/Background: This study examined the effect of adjunctive minocycline on body metabolism in risperidone-treated patients with schizophrenia. Methods/Procedures: Each subject had a Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition diagnosis of schizophrenia and had been on stable dose of risperidone for at least 4 weeks. In a 16-week randomized, double-blind, placebo-controlled study, subjects received either minocycline (200 mg/d) or placebo. Various metabolic parameters, including weight, waist circumference, fasting insulin, glucose, and lipids, were measured at baseline and week 16. Findings/Results: A total of 63 subjects with schizophrenia were enrolled in the study. Fifty-five patients completed week-16 assessments (27 in the minocycline group, 28 in the placebo group). There were no significant differences between the 2 groups in week 16 changes for body weight, body mass index, waist circumference, fasting insulin, glucose, and lipids ( P 's > 0.300). Implications/Conclusions: In the present study, adjunctive treatment of minocycline did not seem to improve body metabolism in patients with schizophrenia receiving risperidone. The implications for future studies were discussed.